COMPREHENSIVE TREATMENT OF PATIENTS WITH CHRONIC RHINITIS - Naumenko, M.; Deyeva, Y.V.; Tarasyuk, N.M. (World of Medicine and Biology, 2016)
During the period from 2004 to 2014 1761 patients with chronic rhinitis (HR) underwent surgery in the ENT department of Rivne CMC. Patients were provided with a wide range of surgical treatment methods, which gave the following results: significant improvement - in 43 (35%), moderate improvement - in 48 (39.0), a slight improvement in 21 (17.1). 11 patients (8.9%) did not appear for a control examination. In conducting the combination therapy clinical recovery was observed in 34 patients (18.1%), a significant improvement - in 92 (48.9%), moderate improvement - in 35 (18.6%), a slight improvement - in 15 (8, 0%); results were not cleared in 12 patients (6.4%). Our studies have shown that more effective treatment of patients with XP is combined treatment with Glutoxim.
Keywords: chronic rhinitis; vasotomiya; septoplastic; konhotomiya; treatment; efficiency; Glutoxim